Strategi Fresh Graduate Universitas Jember dalam Menghadapi Persaingan Pasar Kerja - Erica Natasha Wiyono (Fakultas Ilmu Sosial dan Ilmu Politik, 2026)
This study is motivated by the increasingly intense labor market competition faced by fresh graduates, characterized by the growing number of university graduates that is not proportional to the availability of job opportunities, the high qualification standards set by companies, as well as the importance of work experience and social networks in the recruitment process. These conditions encourage fresh graduates to develop various strategies to enter the labor market and survive in an increasingly competitive environment. This study aims to analyze the strategies employed by fresh graduates of the University of Jember in facing labor market competition. The study is analyzed using Pierre Bourdieu’s theory of social practice, which emphasizes the concepts of habitus, capital, and field. This research employs a qualitative approach with a phenomenological research design to understand the subjective experiences of fresh graduates in dealing with the realities of the labor market. The research subjects were determined using purposive sampling, with the criteria being fresh graduates of the University of Jember who graduated in 2025, including both those who are already employed and those who are still actively seeking jobs. Data validity was tested through source triangulation, while the data analysis techniques included data reduction, data presentation, and conclusion drawing. The findings indicate that fresh graduates of the University of Jember apply various strategies in responding to labor market competition, including capability development through training and certification, the establishment of social networks, and the utilization of social relations to gain access to job vacancy information and employment opportunities. In addition, work readiness is also shaped through cultural capital derived from educational background, organizational experience, internships, and competency certificates that serve as added value in the recruitment process. These findings demonstrate that habitus shapes the way fresh graduates perceive job opportunities, capital functions as a resource in competition, and the labor market field acts as a space with its own rules and power relations in the distribution of opportunities. Keywords: Fresh Graduate, Strategy, Labor Market, Habitus, Capital
FINALISASI oleh Arif 2026 Mei 26
Keywords: FreshGraduates; Strategi; Pasar Kerja; Modal; Habitus